Sporicidal Effects of High‐Intensity 405 nm Visible Light on Endospore‐Forming Bacteria. (30th August 2012) - Maclean, Michelle; Murdoch, Lynne E.; MacGregor, Scott J.; Anderson, John G.
Abstract Resistance of bacterial endospores to treatments, including biocides, heat and radiation is a persistent problem. This study investigates the susceptibility of Bacillus and Clostridium endospores to 405 nm visible light, wavelengths which have been shown to induce inactivation of vegetative bacterial cells. Suspensions of B. cereus endospores were exposed to high‐intensity 405 nm light generated from a light‐emitting diode array and results demonstrate the induction of a sporicidal effect. Up to a 4‐log10 CFU mL−1 reduction in spore population was achieved after exposure to a dose of 1.73 kJ cm−2. Similar inactivation kinetics were demonstrated with B. subtilis, B. megaterium and C. difficile endospores. The doses required for inactivation of endospores were significantly higher than those required for inactivation of B. cereus and C. difficile vegetative cells, where ca 4‐log10 CFU mL−1 reductions were achieved after exposure to doses of 108 and 48 J cm−2, respectively. The significant increase in dose required for inactivation of endospores compared with vegetative cells is unsurprising due to the notorious resilience of these microbial structures. However, the demonstration that visible light of 405 nm can induce a bactericidal effect against endospores is significant, and could have potential for incorporation into decontamination methods for the removal of bacterial contamination including endospores.